Leptospirosis and Rickettsial Diseases Sero-Conversion Surveillance Among U.S. Military Personnel in Honduras - Chao, Chien-Chung; Zhang, Zhiwen; Belinskaya, Tatyana; Chen, Hua-Wei; Ching, Wei-Mei (Military medicine, 2022)
ABSTRACT Introduction Leptospirosis and rickettsial diseases are global zoonotic diseases. In severe infection cases, mortality can range from 10% to 30%. Currently most epidemiological data available are based on outbreak investigations and hospital-based studies from endemic countries. The U.S. soldiers at military bases in these countries are highly vulnerable due to the fact that most of them are immunologically naïve to these pathogens. No risk assessment of leptospirosis and rickettsial diseases among U.S. military personnel in Honduras is currently available. This study was aimed at determining the prevalence of leptospirosis and rickettsial diseases in U.S. military personnel deployed to Honduras using serological assays. Materials and Methods A cohort of pre- and post-deployment sera from the most recent 1,000 military personnel stationed in Honduras for at least 6 months between 2000 and 2016 was identified for this study. Serum specimens from these eligible subjects were retrieved. All post-deployment serum specimens were screened at a dilution of 1:100 for the presence of IgG antibodies to Leptospira and Rickettsia pathogens. The pre-deployment sera from those individuals with post-deployment IgG antibodies above cutoff (i.e., seropositive) were tested to determine seroconversion. Seroconversion was defined as conversion of an optical density value from below the cutoff (i.e., negative) in a pre-deployed specimen to above the cutoff (i.e., positive) in a post-deployed specimen at a titer of 100. Results The seropositive post-deployment specimens for antibodies against Leptospira (causing leptospirosis), Rickettsia typhi (causing murine typhus [MT]), spotted fever group rickettsioses (SFGR, causing SFG Rickettsia), Orientia tsutsugamushi (causing scrub typhus [ST]), and Coxiella burnetii (causing Q fever [QF]) were 11.6%, 11.3%, 6%, 5.6%, and 8.0%, respectively. The seroconverted rate in those assigned to Honduras from 2000 to 2016 was 7.3%, 1.9%, 3.9%, 4.3%, and 2.7% for leptospirosis, MT, SFGR, ST, and QF, respectively. Among the seroconverted specimens, 27 showed seroconversion of at least two antibodies. These seroconverted individuals accounted for 8.8% (3 out of 34) of the personnel who looked for medical attention during their deployment. Conclusions Our results suggest a leptospirosis seroconversion rate of 7.3%, which is higher than the 0.9% and 3.9% seroconversion in Korea and Japan, respectively. The higher rate of seroconversion indicates potential risk of Leptospira exposure. Additional testing of water samples in the pools and pits around the training sites to locate the infected areas is important to eliminate or reduce future exposure to Leptospira during trainings. The rates of seroconversion for ST, MT, spotted fever Rickettsia, and QF were 4.3%, 1.9%, 3.9%, and 2.7%, respectively, indicating the potential exposure to a variety of rickettsial-related pathogens. Testing of vectors for rickettsial pathogens in the areas could inform effective vector control countermeasures to prevent exposure. Proper precaution and protective measures are needed to better protect military personnel deployed to Honduras.